Familial Recurrent Myocarditis Triggered by Exercise in Patients With a Truncating Variant of the Desmoplakin Gene. Issue 10 (18th May 2020) - Poller, Wolfgang; Haas, Jan; Klingel, Karin; Kühnisch, Jirko; Gast, Martina; Kaya, Ziya; Escher, Felicitas; Kayvanpour, Elham; Degener, Franziska; Opgen‐Rhein, Bernd; Berger, Felix; Mochmann, Hans‐Christian; et al.
Abstract : Background: Variants of the desmosomal protein desmoplakin are associated with arrhythmogenic cardiomyopathy, an important cause of ventricular arrhythmias in children and young adults. Disease penetrance of desmoplakin variants is incomplete and variant carriers may display noncardiac, dermatologic phenotypes. We describe a novel cardiac phenotype associated with a truncating desmoplakin variant, likely causing mechanical instability of myocardial desmosomes. Methods and Results: In 2 young brothers with recurrent myocarditis triggered by physical exercise, screening of 218 cardiomyopathy‐related genes identified the heterozygous truncating variant p.Arg1458Ter in desmoplakin. Screening for infections yielded no evidence of viral or nonviral infections. Myosin and troponin I autoantibodies were detected at high titers. Immunohistology failed to detect any residual DSP protein in endomyocardial biopsies, and none of the histologic criteria of arrhythmogenic cardiomyopathy were fulfilled. Cardiac magnetic resonance imaging revealed no features associated with right ventricular arrhythmogenic cardiomyopathy, but multifocal subepicardial late gadolinium enhancement was present in the left ventricles of both brothers. Screening of adult cardiomyopathy cohorts for truncating variants identified the rare genetic variants p.Gln307Ter, p.Tyr1391Ter, and p.Tyr1512Ter, suggesting that over subsequent decades critical genetic/exogenous modifiers drive pathogenesis from desmoplakin truncations toward different end points. Conclusions: The described novel phenotype of familial recurrent myocarditis associated with a desmoplakin truncation in adolescents likely represents a serendipitously revealed subtype of arrhythmogenic cardiomyopathy. It may be caused by a distinctive adverse effect of the variant desmoplakin upon the mechanical stability of myocardial desmosomes. Variant screening is advisable to allow early detection of patients with similar phenotypes.